Pelafalan Huruf Hijaiyyah Yang Benar Harus Sesuai Dengan Makhârij Al- Hurûf dan Karakteristiknya - Ahmad Haris Muchsin Aziz; Muhammad Soleh Ritonga (Al Ashriyyah, 2019)
Reading the Al-Qur'an does not just read, there are things that must be learned and considered. The truth is the reading can be seen from the pronunciation of the letters Hijaiyyah. The pronunciation of the letters must be in accordance with several things. But the underlying for beginners, there are two things that are interrelated. These two things are Makhârij al-Hurûf and Shifât al-Hurûf (Characteristics of Letters). The sound of the pronounced Hijaiyyah letter corresponds to the place where the sound of the Hijaiyyah letter comes out and some of the characteristics of the letter. To be able to know Makhârij al-Hurûf and Shifât al-Hurûf certainly must be learned and practiced.